2016
DOI: 10.3389/fpls.2016.01371
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Biofortification in Radish Enhances Nutritional Quality via Accumulation of Methyl-Selenocysteine and Promotion of Transcripts and Metabolites Related to Glucosinolates, Phenolics, and Amino Acids

Abstract: Two selenium (Se) fertilization methods were tested for their effects on levels of anticarcinogenic selenocompounds in radish (Raphanus sativus), as well as other nutraceuticals. First, radish was grown on soil and foliar selenate applied 7 days before harvest at 0, 5, 10, and 20 mg Se per plant. Selenium levels were up to 1200 mg Se/kg DW in leaves and 120 mg Se/kg DW in roots. The thiols cysteine and glutathione were present at 2–3-fold higher levels in roots of Se treated plants, and total glucosinolate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 70 publications
9
97
0
6
Order By: Relevance
“…As in the present work, in another study [19] with radish plants using foliar applications of up to 20 mg Se per plant, no differences were found compared to the control in phenolic compounds. In contrast, in an experiment under field conditions of Allium cepa L. Se applied 50 µg/mL −1 increased the content of total phenolic compounds compared to the control [26].…”
Section: Biochemical Variablessupporting
confidence: 76%
See 1 more Smart Citation
“…As in the present work, in another study [19] with radish plants using foliar applications of up to 20 mg Se per plant, no differences were found compared to the control in phenolic compounds. In contrast, in an experiment under field conditions of Allium cepa L. Se applied 50 µg/mL −1 increased the content of total phenolic compounds compared to the control [26].…”
Section: Biochemical Variablessupporting
confidence: 76%
“…− per plant, the authors [19] reported a decrease in dry weight of leaves and roots by about 35% and 18% respectively. On the other hand, when cultivating the radish plants in a soilless culture, they did not find significant differences in the dry weight of the leaves.…”
Section: Yield and Biomass Productionmentioning
confidence: 92%
“…Research has been conducted to apply selenium to crops (such as broccoli) to enhance nutritional properties 129 . Studies have shown that excess selenium application can reduce GSL content by 90% 30 .…”
Section: Selenium Applicationmentioning
confidence: 99%
“…cicla). Selenium effects in these plants had previously been [21][22][23][24][25][26][27], except for chard. Raphanus sativus belongs to Brassicaceae -a family of plants cataloged as primary accumulators of selenium and capable of synthesizing low molecular mass methyl-seleno compounds; as for nutritional value, this plant presents relatively high content of glucosinolates, phenolic compounds, vitamins, phytochemicals with possible anticancer activity, anthocyanins and is a good source of elements such as, K , Ca and Mg [28,29].…”
Section: Introductionmentioning
confidence: 99%